The Effects of the Combination of Hyaluronic Acid, Malva sylvestris, and Sodium Alginate on the Pharyngolaryngeal Reflux: A Randomized Case-Control Study - Monda, Alessandro; Genchi, Gemma; Barbara, Francesco; Cariti, Francesco; Russo, Cosimo; Ciccarone, Silvana; Anzivino, Roberta; Plantone, Francesca; Pontillo, Vito; Quaranta, Nicola Antonio Adolfo; Barbara, Michele (Current topics in nutraceuticals research, 2025)
Laryngopharyngeal reflux is an inflammatory condition affecting the tissues of the upper aerodigestive tract, caused by the reflux of gastric or duodenal contents. Unlike gastroesophageal reflux disease, this condition does not necessarily present with typical symptoms such as heartburn or inflammation of the esophagus, making its diagnosis more complex. This study evaluates the effectiveness of a treatment based on hyaluronic acid, Malva sylvestris, and sodium alginate in reducing the symptoms and clinical signs of the disease. A prospective study with a control group was conducted on 30 patients affected by this condition, randomly assigned either to a group receiving the combination of active ingredients or to a control group following only an anti-reflux diet. Clinical outcomes were assessed at the beginning of the study, after 1 month, and after 3 months. The treatment showed a significant improvement in symptoms compared to the control group, with no reported adverse effects. These findings suggest that this combination of active ingredients could represent a valuable complementary therapeutic option, although further studies are needed to confirm its effectiveness.